DARI GOOD GOVERNANCE KE SOUND GOVERNANCE: REFORMASI PRINSIP DAN REGULASI PELAYANAN PUBLIK DI BADAN PENANAMAN MODAL DAN PELAYANAN PERIZINAN TERPADU KABUPATEN LIMA PULUH KOTA - Nasrizal - -; Afriva Khaidir; Syamsir - - (Jurnal Public Administration, Business and Rural Develoment Planning, 2019)
This research is start from the various problems in practical reformation and inovation oflocal goverment in public service realization, especially in implementation of investmentaffair and integrated license service. Based on data and result of analysis are found thatrealization of reformation and public service inovation in Board of Investment andIntegrated License Service at Lima Puluh Kota Regency is not running well. Reformationpractical and public sevice inovation all this time have many problems because of minimumbudget factor, less of human resources, minimum of tools and infrastructures andinformation technology. Public service approach that are used is based on goodgovernance principles with Structural Adjustment Programs (SAPs) pattern that havestandardized in Standard Operational System (SOP) that tend to awkward and thedimensions of sound governance is not fulfill yet. Based on the riil condition fromrealization of reformation and inovation that public service, it can be arranged the ideas toreform the principle and public service regulation in Board of Investment and IntegratedLicense Service at Lima Puluh Kota Regency.